International corporate governance and regulation - John, Kose; Makhija, Anil K.; Ferris, Stephen P. (Advances in financial economics, 2018)
Chapter 1. Climate Policies with Burden Sharing: The Economics of Climate Financing; Julia M. PuaschunderChapter 2. Board Gender Diversity and Firm Financial Performance: A Quantile Regression Analysis; Amelie Charles, Rey Dang, Etienne Redor Chapter 3. Are Dividends an Outcome of or a Substitute for External Corporate Governance? International Evidence based on Product Market Competition; Bobby Alexander, Stephen P. Ferris, Sanjiv Sabherwal Chapter 4. International Evidence on Economic Freedom, Governance, and Firm Performance; Min-Yu Liao Chapter 5. Should We Trust Fund Managers? A Close Look at the Canadian Mutual FundGovernance; Zhongzhi (Lawrence) He, Martin Kusy, Deepak Singh, Samir Trabelsi Chapter 6. The influence of corporate governance mechanisms on the behavior of financial analysts of US firms; Bouteska Ahmed Chapter 7. Corporate governance that influences an investment intention in the ASEAN Stars Thai Listed companies: A marketing application for brokerage firms; Wasukarn Ngamchom, Malai Kamolsakulchai, Thanomsak Suwannoi, Jutamas Wongkantarakorn Chapter 8. Reconsidering the mandate of the audit committee: evidence from corporate governance in Israel; Omer Berkman, Shlomith D. Zuta